'Metal'-like transport in high-resistance, high aspect ratio two-dimensional electron gases. (9th December 2015) - Backes, Dirk; Hall, Richard; Pepper, Michael; Beere, Harvey; Ritchie, David; Narayan, Vijay
Abstract: We investigate the striking absence of strong localisation observed in mesoscopic two-dimensional electron gases (2DEGs) (Baenninger et al 2008 Phys. Rev. Lett . 100 016805, Backes et al 2015 arXiv:1505.03444) even when their resistivity . In particular, we try to understand whether this phenomenon originates in quantum many-body effects, or simply percolative transport through a network of electron puddles. To test the latter scenario, we measure the low temperature (low- T ) transport properties of long and narrow 2DEG devices in which percolation effects should be heavily suppressed in favour of Coulomb blockade. Strikingly we find no indication of Coulomb blockade and that the high- ρ, low- T transport is exactly similar to that previously reported in mesoscopic 2DEGs with different geometries. Remarkably, we are able to induce a 'metal'-insulator transition (MIT) by applying a perpendicular magnetic field B . We present a picture within which these observations fit into the more conventional framework of the 2D MIT.